Fecal Incontinence Due to Occult Obstetrical Anal Sphincter Injuries in Primiparous Women: A Case Report - Igsana Chyntia Murti; Muhamad Nofa Cholili; Dhian Eka Putri Harnandari; Rahajeng (Asian Journal of Health Research, 2024)
Introduction: A predisposing factor for fecal incontinence in women is vaginal birth, impacting between 24 and 44% of the female population. Fecal incontinence, characterized by the inadvertent expulsion of gas or excrement, constitutes a multifactorial condition. It causes discomfort and diminishes the quality of life for women. Owing to its occurrence in 0.6–9% of vaginal deliveries, obstetric anal sphincter injury (OASI) has been identified as the most prevalent cause of AI in young women, with a 15–61% incidence rate following primary repair. Case Presentation: The case presented in this report involved a 26-year-old woman who presented with symptoms of difficult-to-control flatulence and defecation following vaginal delivery. The patient has a history of giving birth to her first child spontaneously at a midwife in June 2023; she found a tear in the birth canal, which was then stitched up. Another history of past illness has been unremarkable. Upon examination, vital signs were within normal limits. The patient was obese I, with a BMI of 27.3 kg/m2. Local examination of external genitalia within normal limits. A digital rectal examination showed that the anal sphincter was not palpable, the rectal mucosa was smooth, and other examinations were within normal limits. Lab examination showed normal results. Conclusion: After an exhaustive examination, a diagnosis of fecal incontinence was made for the patient. The patient was treated with colporrhaphy and sphincterorrhaphy, both of which produced favourable outcomes.